PENGARUH KEBIJAKAN INSNETIF PAJAK PENGHASILAN TERHADAP KEPATUHAN WAJIB PAJAK: DIGITALISASI PAJAK SEBAGAI VARIABEL MODERASI (Studi Empiris Pada UMKM Skala Menengah Di Kecamatan Sirimau Kota Ambon) - Aldi Alfardo Titahena; Linda Grace Loupatty (ADISAM PUBLISHER, 2025)
This research aims to determine the effect of income tax incentive policies on taxpayer compliance: tax digitalization as a moderating variable (empirical study of medium-scale MSMEs in Sirimau District, Ambon City). The method used in this research is a quantitative descriptive method. In collecting data, this research used a saturated sampling technique with the data source used, namely primary data. The population in this study were MSME taxpayers in Sirimau District, Ambon City with a sample size of 32 respondents. The data analysis techniques used are descriptive statistics, classical assumption tests and multiple linear analysis. The hypothesis testing design used is the normality test, multicollinearity test, heteroscedasticity test, t test and coefficient of determination. The analysis tool uses SPSS version 22. Based on the results of the tests carried out, the research results show that: 1) Tax Incentive Policy has a significant positive effect on MSME Taxpayer Compliance, 2) Tax Incentive Moderation and Tax Digitalization has a significant positive effect on Taxpayer Compliance